Electronic Gaming and the Obesity Crisis. Issue 139 (8th March 2013) - Calvert, Sandra L.; Staiano, Amanda E.; Bond, Bradley J.
Abstract: Children and adolescents in the United States and in many countries are projected to have shorter life spans than their parents, partly because of the obesity crisis engulfing the developed world. Exposure to electronic media is often implicated in this crisis because media use, including electronic game play, may promote sedentary behavior and increase consumption of high‐calorie foods and beverages that are low in nutritional value. Electronic games, however, may increase children's physical activity and expose them to healthier foods. We examine the role of electronic games in the pediatric obesity crisis and their contribution to more favorable health outcomes. © 2013 Wiley Periodicals, Inc.